The Effect of Endotoxin on the Intestinal Mucus Layer in Non- and Post-pregnancy Mice - Yan, Dujian; Qiang, Yuyun; Tian, Tian; Lu, Dezhang; Wu, Chenchen (Frontiers in Veterinary Science, 2022)
The intestine is the most extensive storage of bacteria and endotoxins, and the mucosal immune system is the first barrier of intestinal endotoxin invasion. The MUC2 (mucin2) is the major component of the mucus layers. In this study, we explored that MUC2 plays a role in how LPS invades the fetus from the gut to the uterus in pregnant mice. The results showed that the LPS level of ileum, colon and uterus was significantly increased, and the content of sIgA in the ileum, colon and uterus tissues was significantly decreased in the LPS (+) group on the 35th day after LPS treatment. On the 16th day of pregnancy, compared with the LPS (-) group, the level of ileal LPS was significantly decreased, and the content of LPS in the fetus was significantly increased in the LPS (+) group. There was no significant difference in the levels of LPS in the uterus and placenta, and the sIgA content in the fetus was significantly decreased. The expression of MUC2 in the uterus, ileum and colon was increased significantly in the LPS (+) group, especially in the uterus. It is suggested that the endotoxins accumulated in the uterus during non-pregnancy. The high expression of MUC2 in the uterus can prevent LPS from translocating into uterine tissue. It revealed that, after pregnancy, MUC2 still performs the function of protecting the uterine tissue, allowing a large number of LPS to enter the fetal body through blood circulation. Therefore, the level of sIgA significantly decreased, resulting in a decline of the fetal innate immune function.